Designing the future of Pancasila education: A needs analysis for interactive Android-based digital learning materials in primary schools - Nisa A'rafiyah Tri Wulandari; Siti Awaliyah; Siti Utami Dewi Ningrum; Mutia Kamalia Mukhtar; Renda Yuriananta; Erna Risnawati; Mujiono Mujiono; Eka Analita Eliana (Institute of Information Technology and Social Science (IITSS), 2026)
Pancasila education in primary schools is pivotal for early character formation, yet teachers face limited digital teaching media, low learner engagement, and weak technology integration, especially in resource-constrained settings. This study aimed to identify pedagogical, content, and technical requirements for an Android-based application, GO-PANCASILA, for Grade-4 learners. Using a Research and Development approach, the study combined the 4D model (Define, Design, Develop, Disseminate) with the Waterfall SDLC, focusing on the Define and Design phases as a needs analysis. Data were collected through literature review, classroom observations, and semi-structured interviews with teachers and students, then thematically analyzed and triangulated. Findings showed that teachers struggle to create contextual materials, choose relevant methods, and manage instructional time, while students prefer multimedia-based interactive learning. Key needs include engaging visual content, reflective quizzes, and integration of Pancasila values into daily experiences. These findings provide a foundation for developing GO-PANCASILA as an adaptive learning solution supporting character formation and civic literacy.